2004
DOI: 10.1108/00400910410543982
|View full text |Cite
|
Sign up to set email alerts
|

The impact of approaches to learning and cognition on academic performance in business and management

Abstract: Results of a study into the relationships between students' academic performance and their cognitive and learning styles are presented. A questionnaire containing three instruments assessing learning and cognition was distributed to second and final year undergraduates studying on a general and business management degree. The outcomes of this are explored and analysed in relation to the students' selection of modules and performance in assessments.The research explores whether students' approaches to learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
8
1
1
Order By: Relevance
“…These findings are in contrast to previous studies that have found differences in approaches to learning depending on gender (Cano 2005;Picou et al 1998;Rouse and Austin 2002), discipline (Biggs 1987b;Jones et al 2003;Nelson Laird et al 2007;Smith and Miller 2005) and ability (Pyryt et al 1998;Spicer 2004;Wilding and Andrews 2006). While the lack of gender differences might be due to the fact that other factors were included in the model, the lack of differences depending on ability might be due to the fact that the university from which the current student sample was taken admits only academically excellent secondary students, resulting in relatively little variance in this factor compared with other samples.…”
Section: Discussioncontrasting
confidence: 85%
“…These findings are in contrast to previous studies that have found differences in approaches to learning depending on gender (Cano 2005;Picou et al 1998;Rouse and Austin 2002), discipline (Biggs 1987b;Jones et al 2003;Nelson Laird et al 2007;Smith and Miller 2005) and ability (Pyryt et al 1998;Spicer 2004;Wilding and Andrews 2006). While the lack of gender differences might be due to the fact that other factors were included in the model, the lack of differences depending on ability might be due to the fact that the university from which the current student sample was taken admits only academically excellent secondary students, resulting in relatively little variance in this factor compared with other samples.…”
Section: Discussioncontrasting
confidence: 85%
“…Individuals' levels of work drive also explain significant variations in GPA that cannot be explained based on the "big five" factors or intelligence (Allik, 2012;Ridgell and Lounsbury, 2004). The traits of prudence, self-control, dominance and perfectionism, as well as academic discipline and commitment to college, are significant predictors of higher GPAs and remaining in school (Laidra et al, 2007;O'Connell and Sheikh, 2011;Pintrich, 2000;Spicer, 2004). Academic performance is also higher among sociable, emotionally stable and introverted individuals.…”
Section: Personality and Academic Achievementmentioning
confidence: 85%
“…Literature review 2.1 Personality and academic motivation Personalities are seen as stable individual characteristics or attributes that exhibit particular patterns of behaviour, cognitions, and emotions (Allik, 2012;Heaven and Ciarrochi, 2012;Just, 2011;Komarraju et al, 2009;Vesealka et al, 2012). Most existing research on personality has argued that it has five dimensions: extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience (Bartels et al, 2012;Rushton and Irwing, 2009;Spicer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When students can identify and explore their own learning styles, they can also gain awareness of how they might approach learning. They realize they have some control (Spicer, 2004). Felder and Soloman offer this survey free in order to compile more research data.…”
Section: Discussionmentioning
confidence: 99%